Penerapan Slow Deep Breathing Untuk Menurunkan Skala Nyeri Pada Pasien Cedera Kepala Ringan (CKR) Di RSUD Dr. Moewardi Surakarta - Dwi Cahyo Pribadi Putro; Hermawati Hermawati; Isti Wulandari (Jurnal Ilmu Kesehatan dan Gizi, 2023)
Background: Prevalence of patients with mild cedar heads recorded from March to July 2023 in the Emergency Room of RSUD Dr. Moewardi as many as 757 cases, and most of them complained of pain in the head, pain in CKR patients by nurses can be treated with pharmacological and non-pharmacological therapy. Non-pharmacological therapy such as behavioral therapy (relaxation, hypnotherapy, biofeedback). One of the relaxation techniques used is slow deep breathing. Objective: Changes in the application of the Slow Deep Breathing technique to reducing pain scale in mild head injury patients at RSUD Dr. Moewardi. Method : the method used in this application is a descriptive method. In this application, pain scale measurements were carried out using the Numeric Rating Scale both before and after slow deep breathing was carried out. Findings : the results of the implementation that has been done, it was found that respondent I experienced a decrease in the pain scale from a scale of 8 to a scale of 7, respondent II experienced a decrease in the pain scale from a scale of 6 to a scale of 4. Implication : slow deep breathing can reduce the pain scale in patients with mild head injuries at Dr. Moewardi.